Early Initiation of Direct Oral Anticoagulants After Onset of Stroke and Short- and Long-Term Outcomes of Patients With Nonvalvular Atrial Fibrillation. Issue 3 (March 2020) - Mizoguchi, Tadataka; Tanaka, Kanta; Toyoda, Kazunori; Yoshimura, Sohei; Itabashi, Ryo; Takagi, Masahito; Todo, Kenichi; Shiozawa, Masayuki; Yagita, Yoshiki; Yoshimoto, Takeshi; Terasaki, Tadashi; Yamagami, Hiroshi; et al.
Abstract : Background and Purpose—: We aimed to compare outcomes of ischemic stroke patients with nonvalvular atrial fibrillation between earlier and later initiation of direct oral anticoagulants (DOACs) after stroke onset. Methods—: From data for 1192 nonvalvular atrial fibrillation patients with acute ischemic stroke or transient ischemic attack in a prospective, multicenter, observational study, patients who started DOACs during acute hospitalization were included and divided into 2 groups according to a median day of DOAC initiation after onset. Outcomes included stroke or systemic embolism, major bleeding, and death at 3 months, as well as those at 2 years. Results—: DOACs were initiated during acute hospitalization in 499 patients in median 4 (interquartile range, 2–7) days after onset. Thus, 223 patients (median age, 74 [interquartile range, 68–81] years; 78 women) were assigned to the early group (⩽3 days) and 276 patients (median age, 75 [interquartile range, 69–82] years; 101 women) to the late (≥4 days) group. The early group had lower baseline National Institutes of Health Stroke Scale score and smaller infarcts than the late group. The rate at which DOAC administration persisted at 2 years was 85.2% overall, excluding patients who died or were lost to follow-up. Multivariable Cox shared frailty models showed comparable hazards between the groups at 2 years for stroke or systemic embolism (hazard ratio, 0.86 [95% CI, 0.47–1.57]), major bleeding (hazard ratio, 1.39 [95% CI, 0.42–4.60]), and death (hazard ratio, 0.61 [95% CI, 0.28–1.33]). Outcome risks at 3 months also did not significantly differ between the groups. Conclusions—: Risks for events including stroke or systemic embolism, major bleeding, and death were comparable whether DOACs were started within 3 days or from 4 days or more after the onset of nonvalvular atrial fibrillation–associated ischemic stroke or transient ischemic attack. Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01581502. Abstract : Supplemental Digital Content is available in the text.